Synthesis and Screening of a DNA‐Encoded Library of Non‐Peptidic Macrocycles. (2nd March 2022) - Koesema, Eric; Roy, Animesh; Paciaroni, Nicholas G.; Coito, Carlos; Tokmina‐Roszyk, Michal; Kodadek, Thomas
Abstract: There is considerable interest in the development of libraries of non‐peptidic macrocycles as a source of ligands for difficult targets. We report here the solid‐phase synthesis of a DNA‐encoded library of several hundred thousand thioether‐linked macrocycles. The library was designed to be highly diverse with respect to backbone scaffold diversity and to minimize the number of amide N−H bonds, which compromise cell permeability. The utility of the library as a source of protein ligands is demonstrated through the isolation of compounds that bind Streptavidin, a model target, with high affinity. Abstract : The discovery of ligands for the "undruggable proteome" is likely to require the development of new chemical matter with a greater "molecular wingspan" than traditional Lipinski‐compliant small molecules. A DNA‐encoded library (DEL) of non‐peptidic thioether macrocycles has been constructed and screened for high affinity protein ligands to a model protein, SA.